Sucrose synthase 2 regulates whole plant transpiration in Nicotiana tabacum L. - Freire, Francisco Bruno Silva (2020)
Stomata are small structures present primarily in the leaf epidermis of plants, composed of two guard cells that surround and regulate the opening and closing of the stomatal pore. Stomatal movements regulate atmospheric CO2 input for photosynthesis and transpired water output, being thus important for plant water use efficiency, defined by the ratio of CO2 assimilation to transpired water loss. Recent results indicate that the degradation of sucrose is a mechanism responsible for inducing stomatal opening. Additionally, it has been shown that genetic manipulation of guard cell sucrose metabolism is a potential tool for obtaining plants that consume less water and/or having greater water use efficiency. Within this perspective, this study aimed to evaluate the biotechnological potential of genetic manipulation of guard cells saccharolytic activity in the development of drought tolerant and/or more water use efficient plants. Different biochemical and molecular analyzes coupled with an extensive physiological characterization were developed in order to characterize the phenotype of transgenic Nicotiana tabacum plants antisense for the potato sucrose synthase 3 gene (StSUS3) under the control of the stomatal-specific KST1 promoter. The results demonstrated that the inserted transgene (StSUS3) reduced the expression of tobacco NtSUS2 isoform, which consequently altered substantially guard cell metabolism. Also, the plants decreased stomatal conductance and whole plant transpiration rates and increased the water use efficiency, besides the plants presented a drought avoidance phenotype. Taken together, our results indicate that the NtSUS2 gene is a key regulator of plant transpiration and is therefore an important biotechnological target.